2016
DOI: 10.4236/oalib.1102428
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Point-of-Care Testing (POCT) in Reducing Total Waiting Time at Warfarin Clinic of a District Hospital: A Cohort Study

Abstract: G. Kasinathan et al.OALibJ |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Similarly, in the present study, POCT intervention was found to reduce the overall waiting time markedly from 180 minutes to less than 30 minutes. These findings also resonate with the findings of Kasinathan et al [6] On comparing and correlating the results of POCT (with a handheld device) and core laboratory analyzer, an overall good agreement between POCT and laboratory plasma INR results using CLSI 14-A agreement limits and ISO 17593-2007 acceptability criteria of allowable difference within 90% of all results was achieved; this makes the Hemochron POCT device adequate for clinical use. Although ISO 17593-2007 criteria do not pertain to in vitro measuring systems assessing vitamin K antagonist (warfarin) therapy at a health care facility, we applied it to guide individuals who could use such handheld devices to perform INR self-testing for monitoring and or managing their own warfarin therapy.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, in the present study, POCT intervention was found to reduce the overall waiting time markedly from 180 minutes to less than 30 minutes. These findings also resonate with the findings of Kasinathan et al [6] On comparing and correlating the results of POCT (with a handheld device) and core laboratory analyzer, an overall good agreement between POCT and laboratory plasma INR results using CLSI 14-A agreement limits and ISO 17593-2007 acceptability criteria of allowable difference within 90% of all results was achieved; this makes the Hemochron POCT device adequate for clinical use. Although ISO 17593-2007 criteria do not pertain to in vitro measuring systems assessing vitamin K antagonist (warfarin) therapy at a health care facility, we applied it to guide individuals who could use such handheld devices to perform INR self-testing for monitoring and or managing their own warfarin therapy.…”
Section: Discussionsupporting
confidence: 86%
“…10 Consequently, INR monitoring can improve its stability within the therapeutic range and prevent serious complications. 11 Based on the background described above, an evaluation of warfarin use in heart disease patients at Dr. Hasan Sadikin Hospital was conducted to determine the drug use profile, effectiveness, and if the administered therapy dose has reached the target therapeutic INR value of 2 to 3. Dispensation of safe and effective warfarin doses improves the therapy's success and patient's life quality and avoids side effects of bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…During the development of research on major bleeding related to warfarin, the mortality rate reached 9.5-13.4% [7,8]. An examination of the international normalized ratio (INR) in patients receiving warfarin therapy is needed to monitor the chances of bleeding [9,10].…”
Section: Introductionmentioning
confidence: 99%